Development of PAI Learning in the Digital Era Merdeka Curriculum at MTs Negeri 1 Yogyakarta - Mubarok, Ahmad Syahri; Mahdi, Asmin; Basri, Hasan; Zakaria, Abd Razak (Eduprof : Islamic Education Journal, 2023)
Islamic Religious Education (PAI) has a central role in shaping the personality, morality and spiritual values of students. In responding to the challenges of an increasingly global digital era, developing PAI learning in the Merdeka Curriculum has become a crucial aspect in responding to developments in information and communication technology which have changed the way we interact with information, religion and education. This study aims to find out how the development of Islamic religious education learning in the Merdeka Curriculum learning the digital era and find out how the problems of learning Islamic religious education in the Merdeka Curriculum at MTs Negeri 1 Yogyakarta. This research is field research using descriptive qualitative methods. Data collection in this study used interviews, observation and documentation. Analysis techniques use: data reduction, data visualization, and drawing conclusions/verification. Meanwhile, the data validity test takes the form of source triangulation and technical triangulation. The results of this study show that religious education learning in the independent digital era learning curriculum at MTs Negeri 1 Yogyakarta is to provide guidance to students to become individuals who have noble morals and fear Allah Swt. and have the ability to think critically, have the ability to do high activities, be able to communicate well, be able to collaborate and be confident and can utilize technology as a learning medium for Islamic religious education. As for the problems of learning Islamic religious education in the Merdeka Curriculum in the digital era, namely: human resources are not adequate to implement Islamic religious education learning in the digital era, PAI teachers have not mastered the concept of an Merdeka Curriculum and do not have qualified abilities in using technological media in learning, low quality of education, inadequate facilities and infrastructure. So the solution that can overcome the problems of learning Islamic religious education in the digital era is to develop and improve human resources first, provide facilities and infrastructure and utilize technological media in learning Islamic religious education.